A corpus-based study on deontic modality in Competition Law: Insights from the English-Greek language pair - Kozobolis, Stavros (Estudios de Traducción, 2020)
This study investigates deontic modality, the grammatical category through which legal texts express mainly obligation and permission, in an English-Greek bilingual corpus composed of legislative texts related to European Union (EU) Competition Law. More specifically, the study is based on Biel’s discussion on deontic modality, i.e. deontic obligation and deontic permission (Biel 2014: 158). The analysis of the data is mainly quantitative, while a small-scale qualitative analysis is also carried out when necessary. The results of the study are compared with the specific guidelines proposed by the EU Institutions for English and Greek, i.e. the Joint Practical Guide of the European Parliament, the Council and the Commission for persons involved in the drafting of European Union legislation (2015), the English Style Guide: A handbook for authors and translators in the European Commission for English (2018) and the Greek Style Guide: A handbook for authors and translators in the European Commission for Greek (n.d.), as well as with those of earlier studies on legislative texts.